2019
DOI: 10.7759/cureus.5719
|View full text |Cite
|
Sign up to set email alerts
|

Association of Migraine and Ischemic Heart Disease: A Review

Abstract: Many new studies have shown an association between migraine and ischemic heart disease, and the association seems to be multi-factorial. This article reviews what is already known about this linkage and further investigates if migraine is a risk factor for cardiovascular disease.The literature search for this article was performed primarily using PubMed as the search engine. Only those articles that assessed migraine as exposure and cardiovascular events as outcomes were included. Also, articles only from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Numerous studies have also shown migraine to be an important risk factor for ischemic heart disease (IHD), as well as other adverse cardiac events, such as myocardial infarction, angina, and arrhythmia ( 110 , 111 ). Furthermore, research has also found an increased risk of patent foramen ovale, atrial septal defect, and mitral valve prolapse in migraine patients with aura ( 110 , 111 ).…”
Section: Biological Risk Factors and Comorbiditiesmentioning
confidence: 99%
“…Numerous studies have also shown migraine to be an important risk factor for ischemic heart disease (IHD), as well as other adverse cardiac events, such as myocardial infarction, angina, and arrhythmia ( 110 , 111 ). Furthermore, research has also found an increased risk of patent foramen ovale, atrial septal defect, and mitral valve prolapse in migraine patients with aura ( 110 , 111 ).…”
Section: Biological Risk Factors and Comorbiditiesmentioning
confidence: 99%
“…We considered baseline comorbidities of diabetes (ICD-9-CM250), hypertension (401–405), hyperlipidemia (272.0–272.4), arrhythmia (427), thyroid disease (240–246), and migraine (346) potential covariates associated with the development of IHD [ 2 , 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Strong evidence suggested migraine as a risk factor for ischemic stroke. Researches have also shown the positive link between migraine and ischemic heart disease, especially in migraineurs with aura 3 - 5 .…”
Section: Introductionmentioning
confidence: 99%